The Influence of Work Motivation and Employee Competence on Employee Performance through Organizational Citizenship Behavior (OCB) in the Cilegon City Government - Purnamanudin, IC Indra; Yusuf, Furtasan Ali; Nuryanto, Uli Wildan (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
Employee performance in the Cilegon City Regional Government is not optimal, which is influenced by a lack of motivation to work, employee competence, and Organizational Citizenship Behavior (OCB). The purpose of this study is to evaluate how employee work motivation and competence impact their performance, both directly and indirectly, by using OCB as a mediating variable. Various issues are discussed, including: (1) the relationship between work motivation and employee performance; (2) the relationship between work motivation and OCB; (3) the relationship between employee competence and OCB; (4) the relationship between OCB and employee performance; and (6) the mediating role of OCB in the relationship between work motivation and employee competence. This study uses a quantitative method, namely PLS-SEM, or Partial Least Square-Structural Equation Modelling. The research instrument is a questionnaire that has been tested for validity and reliability, with respondents from State Civil Apparatus (ASN) selected through random sampling. The results show that work motivation and competence have a significant positive effect on employee performance and OCB, and OCB acts as a significant mediator. Recommendations are given to the Cilegon City Regional Government to increase motivation, competence, and the cultivation of OCB to encourage sustainable employee performance.